HISTORY OF THE DEVELOPMENT OF LEGISLATIVE REGULATION OF CRIMINAL LIABILITY FOR CRIMES INVOLVING PERSONAL FREEDOM - Широкоступ, Катерина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: to carry out a historical and legal analysis of the regulation of the peculiarities of criminal liability for crimes against human freedom before the adoption of the current Criminal Code of Ukraine. Research methods: the research was conducted using general scientific methods, such as dialectical analysis and synthesis, abstraction, deduction and induction, and special methods, such as formal legal, interpretation of law, comparative legal method and others. The empirical basis was the legal acts of Ukraine and foreign countries, scientific works related to this issue. Results: the article analyzes the genesis and development of special features of criminal liability for crimes that infringe on personal freedom in accordance with the laws in force in Ukraine since the beginning of the eighteenth century. Until the adoption of the current Criminal Code of Ukraine. It is determined that the legislative regulation of criminal liability for crimes against personal liberty has a long and interesting history. Lawyers of the nineteenth century did not have a clear enough idea of the object of the crime, namely the personal freedom of man, so the responsibility for these actions was scattered in various structural parts of the then regulations. Over time, legislators have come to the conclusion that it is necessary to carry out criminal protection of personal freedom. As for the responsibility for hostage-taking, it was enshrined in law only in 1987. Discussion: a study of the history of development and the feasibility of applying the experience of legislative regulation of criminal liability for crimes that infringe on personal freedom.